Cytoskeletal and morphologic impact of cellular oxidant injury. - Hinshaw, D. B. (1986)
The relationship between changes in cell morphology and the cytoskeleton in oxidant injury was examined in the P388D1 cell line. Flow cytometry of cells stained with NBD-phallacidin, a fluorescent probe specific for filamentous (F) actin, revealed a substantial increase in F actin content in H2O2-injured cells over 3-4 hours. Doses of H2O2 as low as 500 microM produced sustained increases in F actin content. Experiments where catalase was used to interrupt H2O2 exposure over a long time course revealed 15-30 minutes to be the critical period of exposure to 5 mM H2O2 necessary for a sustained increase in F actin as well as large increases in membrane blebbing and later cell death. The increase in F actin with H2O2 injury was confirmed with the use of electrophoresis in acrylamide gels of 1% Triton X-100 cytoskeletal extracts from P388D1 cells. Scanning electron microscopy revealed major loss of surface convolutions in addition to the formation of blebs. Fluorescence microscopy of adherent cells using rhodamine phalloidin showed considerable cell rounding and rearrangement of cellular F actin by 30 minutes of exposure to H2O2. Transmission electron microscopy revealed side to side aggregation of F actin bundles (microfilaments) developing during this time. Considerable swelling of mitochondria and other subcellular organelles was seen after 2 hours of injury. The apparent area of attachment to the substrate was markedly diminished in injured cells. H2O2 injury produced a marked increase in F actin with an associated rearrangement of the microfilaments and simultaneous changes in the plasma membrane prior to cell death in the P388D1 cell line.